2011
DOI: 10.1093/aje/kwr005
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Obesity and Age-related Macular Degeneration

Abstract: Evidence for an association between age-related macular degeneration (AMD) and obesity is inconsistent. The authors examined associations between adiposity and AMD prevalence using 21,287 participants from the Melbourne Collaborative Cohort Study aged 40-69 years at baseline (1990-1994). For men, each increase of 0.1 in waist/hip ratio (~1 standard deviation) was associated with a 13% increase in the odds of early AMD (odds ratio = 1.13, 95% confidence interval: 1.01, 1.26; P = 0.03) and a 75% increase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 62 publications
1
61
0
7
Order By: Relevance
“…Along with the covariates already mentioned, education, body composition, genetics, diet and alcohol were included in the directed acyclic graph as they have previously been associated with the risk of AMD 18–21. Interactions between PA and sex were explored as exercise and PA patterns differ considerably between the sexes and interaction by sex has previously been reported when investigating the association between cardiovascular risk factors and AMD 20 22 23…”
Section: Methodsmentioning
confidence: 99%
“…Along with the covariates already mentioned, education, body composition, genetics, diet and alcohol were included in the directed acyclic graph as they have previously been associated with the risk of AMD 18–21. Interactions between PA and sex were explored as exercise and PA patterns differ considerably between the sexes and interaction by sex has previously been reported when investigating the association between cardiovascular risk factors and AMD 20 22 23…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Adams et al found that a 0.1 waist/hip ratio increase was correlated with a 13% chance increase of developing early AMD (P=0.03), and a 75% chance increase of developing late AMD (P=0.02). However, an inverse relationship was seen between waist/hip ratio and risk of AMD with women (Adams et al, 2011). Schaumberg et al found that increased body mass index was correlated with dry AMD in men.…”
Section: Biomarkers Of Susceptibilitymentioning
confidence: 99%
“…ApoE is the major apolipoprotein of the CNS and an important regulator of cholesterol and lipid transport (Klaver et al, 1998). Since then, the ApoE gene, found on chromosome 19q13.2 (Adams et al, 2011), has been consistently shown to play a significant role in the development of AMD (Baird et al, 2004; Levy et al, 2015; Paun et al, 2015). The ApoE polymorphism rs2075650 has been strongly associated with early AMD (P=1.1x10 −6 ) (Holliday et al, 2013).…”
Section: Biomarkers In Heritability and Geneticsmentioning
confidence: 99%
“…World Health Organization (WHO) global eye disease survey has revealed that more than 50 million people are affected with AMD and atleast one-third of them are blind or severely visually impaired [163]. Development of AMD is multifactorial including aging, smoking, genetic factors, obesity, hypertension and hypercholesterolemia [164-168]. The disease is characterized by degeneration of central retina leading to disturbed fine and color vision.…”
Section: Role Of Hif-1 In Ocular Diseasesmentioning
confidence: 99%